The application of metagenomic next-generation sequencing in patients with infection or colonization caused by Lichtheimia species - Chen, Lihua; Peng, Weiting; Lan, Gongbin; Long, Guo; Yang, Honghui; Xu, Yajing; Fu, Ai; Yi, Huimin; Wan, Qiquan (Frontiers in Cellular and Infection Microbiology, 2023)
Background Mucormycosis is considered the fourth most common invasive fungal disease after candidiasis, aspergillosis and cryptococcosis. Lichtheimia species accounted for 5%-29% of all mucormycosis. However, available data on species-specific analysis of Lichtheimia infections are limited. Methods This study included nine patients hospitalized in five hospitals in two cities in south China with mucormycosis or colonization caused by Lichtheimia species, diagnosed mainly by metagenomic next-generation sequencing (mNGS). The corresponding medical records were reviewed, and the clinical data analyzed included demographic characteristics, site of infection, host factors and type of underlying disease, diagnosis, clinical course, management, and prognosis. Results In this study, nine patients with Lichtheimia infections or colonization had a recent history of haematological malignancy (33.3%), solid organ transplants (33.3%), pulmonary disease (22.2%), and trauma (11.1%) and were categorized as 11.1% (one case) proven, 66.7% (six cases) probable mucormycosis and 22.2% (two cases) colonization. Pulmonary mucormycosis or colonization was the predominant presentation in 77.8% of cases and mucormycosis caused by Lichtheimia resulted in death in four out of seven patients (57.1%). Conclusion These cases highlight the importance of early diagnosis and combined therapy for these sporadic yet life-threatening infections. Further studies on the diagnosis and control of Lichtheimia infection in China are required.